VERIFICATION OF ROUGHNESS IN A PROTOTYPE OF A WETBLASTING SURFACE FINISHING PROCESS ON AISI 304 STAINLESS STEEL. - Sanchez Monsalve, Luz Stella S
Stainless steel is a material widely used invarious applications, and some of these applicationshave specific requirements in terms of roughnessand surface finish. In the particular case of the foodindustry, food process equipment manufacturingorganizations have deficiencies in obtainingrecommended roughness values that comply withexisting regulations.To produce surfaces with the rightroughness, one of the methods to perform thisthe finishing process is wet blasting, with this processcharacters can be obtained with a roughness suchthat they contribute to meeting the necessaryconditions of safety and that prevent the adhesionof bacteria.The company Ingeniar Inox SASthrough the formulation of project SENNOVA- Minciencias para la Innovación carried outa functional prototype of a cabin for the Wetblasting process including this methodology in theproduction process and carrying out laboratory testswith the support of Tecnoparque SENA Pereiraand GIMI Grupo de Investigaciones en Materialesde Ingeniería UTP applying the tests on samples ina function with defined parameters and finding asatisfactory average roughness result of 0.213 µmwhich is in the recommended range.